Youth and crime - Muncie, John (London : SAGE, 2021)
"The most comprehensive and authoritative textbook on youth crime and youth justice. Extensively updated to reflect changes in the youth justice system and contemporary debates around youth crime, this fifth edition of Youth and Crime: includes new chapters on developmental and life course theories, and punitive justice strategies, has been significantly expanded with new sections on the politicisation of youth crime, knife crime and gangs, child refugees, climate justice, child-on-child homicide, and localised criminal exploitation, features increased coverage of policing strategies, including sections on policing public space and rethinking youth justice.Complete with a new two colour design, chapter outlines, summary boxes, study questions, further reading lists, useful website lists, and a glossary, this textbook expertly guides students through their studies in youth and crime." -- provided by publisher.
1: Images of youth and crime -- 2: Histories of youth and crime -- 3: Explaining youth crime I: positivist criminologies -- 4: Explaining youth crime II: developmental and life course theories -- 5: Explaining youth crime III: radical and realist criminologies -- 6: Youth victimology -- 7: Youth cultures, cultural studies and cultural criminology -- 8: Youth and social policy: control, regulation and governance -- 9: Youth justice strategies I: welfare and justice -- 10: Youth justice strategies II: policing, prevention and risk management -- 11: Youth justice strategies III: custody, punishment and rights -- 12: Comparative and international youth justice.
Previous edition: 2015.
Includes bibliographical references (pages 477-536) and index.
Keywords: Criminal behavior; Juvenile delinquency; Criminal behavior; Juvenile delinquency